Sardar Patel: The iron man of India - Tripathi, Satya Prakash Mani (New Delhi Trans-India Book, 2020)
Iron Man of India, Patel and Farmer$1 (Bs Movements, Princely State and Patel , Patel and Quit India Movement s
Keywords: Social Activist, Nation Builder, Bharat ratna Awarded